Double is better: achieving an oxide solar-blind UV detector with ultrahigh detectivity and fast-refreshing capability. (December 2022) - Zhu, Rui; Liang, Huili; Bai, He; Zhu, Tao; Mei, Zengxia
Highlights: By adopting a periodic bias-switching working method, the PPC is stably suppressed. The insertion of this VO -poor a-Ga2 O3 layer assures the formation of good Schottky contact. The detector with double Ga2 O3 layers obtains ultra-high detectivity and UV-vis rejection ratio. The device with no special passivation and encapsulation is still working normally after such a long time. The marvelous merit of the double-layer device is the negligible refresh time, which is just the time to reverse the bias voltage. Abstract: Oxygen vacancy (VO ) defects are common in oxide semiconductors, which are generally believed to be double-edged in detectors. They contribute to a photo gain effect and consequently high responsivity. However, VO defects typically result in high dark current and long persistent photoconductivity (PPC), severely affecting the weak-light detecting and quick refreshing abilities. Here, a simple two-terminal architecture is constructed on amorphous Ga2 O3 double layers. By adopting a periodic bias-switching working method, we found that the PPC is stably suppressed and a robustly high refresh rate is achieved, accompanied with the ultra-high photo-to-dark current ratio (>10 9 ), detectivity (8.7×10 17 Jones) and UV-vis rejection ratio (>10 8 ). The combination of VO -gradient double-layer structure and new working method enables an unimpeded transportation of photo-generated electrons under light illumination and a swift block of the trap-released electrons in dark. The methodology may be hopefully extended to other oxide semiconductors for high-performance photodetection.